Klasifikasi Glaukoma Menggunakan Artificial Neural Network - Alva Rischa Qhisthana Pratika; Rita Magdalena; R Yunendah Nur Fuadah (Jurnal Ilmiah FIFO, 2020)
Abstract Glaucoma is an eye disease caused by increased eyeball pressure resulting in damage to the optic nerve and the second leading cause of blindness after cataracts. Nerve damage often occurs without symptoms so that an early examination can reduce the risk of glaucoma. Therefore, the authors designed a glaucoma detection system through eye fundal images that can facilitate the detection of glaucomaby extracting various features like Rim to Disc Ratio, Cup to Disc Ratio (CDR), Vertical Cup to Disc Ratio (VCDR), Horizontal Cup to Disc Ratio (HCDR), and Horizontal to Vertical CDR (H-V CDR) with Morphological Operations dan Thresholding for segmentation of Optic Disc (OD) and Optic Cup (OC). Artificial Neural Network (ANN) is used as a classifier of glaucoma. Through this method, the test data can be divided into two classifications namely normal eyes and glaucoma eyes. 62 pieces of data will be trained and 62 pieces of data will be tested. The results obtained aim to facilitate early detection of glaucoma eyes. Accuracy on training data reaches 100% and accuracy in this study is reached 93.5484%.Keyword: Glaucoma, Morphological Operation, Thresholding, Artificial Neural Network AbstrakGlaukoma adalah penyakit mata yang disebabkan oleh peningkatan tekanan bola mata sehingga terjadi kerusakan saraf optik dan dapat menyebabkan kebutaan nomor dua setelah katarak. Kerusakan saraf sering terjadi tanpa gejala sehingga pemeriksaan dini dapat mengurangi resiko dari glaukoma. Oleh karena itu, penulis merancang suatu sistem untuk mendeteksi glaukoma melalui citra fundus mata dengan mengekstraksi beberapa fitur yaitu Rim to Disc Ratio, Cup to Disc Ratio (CDR), Vertical Cup to Disc Ratio (VCDR), Horizontal Cup to Disc Ratio (HCDR), dan Horizontal to Vertical CDR (H-V CDR) dengan mengsegmentasi Optic Disc (OD) dan Optic Cup (OC) dengan menggunakan metode Morphological Operations dan Thresholding. Artificial Neural Network (ANN) digunakan sebagai metode klasifikasi glaukoma. Melalui metode tersebut, data uji dapat dibagi dalam dua klasifikasi yaitu mata normal dan mata glaukoma. Data latih yang akan diambil sebanyak 62 buah dan data uji yang akan diambil sebanyak 62 buah. Hasil yang diperoleh bertujuan untuk memudahkan mendeteksi secara dini mata glaukoma. Akurasi pada data latih mencapai 100% dan akurasi pada data uji mencapai 93,5484%.Kata kunci: Glaukoma, Morphological Operation, Thresholding, Artificial Neural Network